(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article examines methods for organizing population protection in emergencies caused by fire and explosion. Emphasis is placed on understanding fire and explosion hazards, preparing protective measures, and effectively mobilizing resources for immediate response and recovery. Through literature review and case studies, the paper aims to highlight the best practices and innovative approaches in ensuring the safety of individuals and communities. Recommendations for improving existing frameworks are also provided.